1995
DOI: 10.1007/bf00290710
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of somatic meiosis in embryogenic carrot cell cultures

Abstract: During the establishment of an embryogenic cell line from a carrot hypocotyl explant, processes closely resembling meiotic divisions are seen. A microdensitometric analysis revealed that the amount of cellular DNA diminished in the majority of cells to the haploid level. However, the diploid level was re-established in a matter of a few days. The genetic consequences of this segregation were studied by analyzing restriction fragment length polymorphisms (RFLP) and randomly amplified polymorphic DNAs (RAPD). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The recovery oflost sequences, as described in our previous (GIORGETTI et al 1995;GERI et al 1999) and present papers, is not new in biology: particularly in plant science, amplification and under-replication of sequences have been extensively described since the nineteen-seventies. Sequence amplifications occur in plant cells under many circumstances (PARENTI et al 1973;Nun RoNCHI et al 1973), and can follow the general model of sequence amplification described in two recent erudite reviews (TowER 2004;CLAYCOMB and 0RR-WEAVER2005).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The recovery oflost sequences, as described in our previous (GIORGETTI et al 1995;GERI et al 1999) and present papers, is not new in biology: particularly in plant science, amplification and under-replication of sequences have been extensively described since the nineteen-seventies. Sequence amplifications occur in plant cells under many circumstances (PARENTI et al 1973;Nun RoNCHI et al 1973), and can follow the general model of sequence amplification described in two recent erudite reviews (TowER 2004;CLAYCOMB and 0RR-WEAVER2005).…”
Section: Discussionmentioning
confidence: 53%
“…the systematic difference between the genetic and physical maps of the same chromosome that appears to occur about as universally as meiosis itself (EGEL 1995) and is rationalized, on a molecular basis, by the loss of somatic sequences that reduces the chromosome length available to crossing over (KAGAWA et al 2002). Somatic embryogenesis data (GIORGETTI et al 1995;GERI et al 1999), as well as the results from in vivo meiosis presented in this paper, suggest that the phenomenon of chromatin diminution before gamete formation described herein could be likened to a process of germ-line formation; indeed somatic cells are reset before entering meiosis, acquiring a status of typical germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover our previous results from other plant species demonstrated that proliferating primary explants invariably undergo processes mimicking sexual maturation, included somatic meiosis and fl oral-like primordia differentiation (GIORGETTI et al 1995;GERI et al 1999;PITTO et al 2001). These events occur in somatic cultured cells very early in vitro, and their outcome is due to a genetic reprogramming that, while erasing the previous information related to the somatic differentiated status, directs the committed cells to a gamete-like state (totipotency), prerequisite for embryogenesis or regeneration.…”
Section: Polyploidization-inducing Mechanisms: A) Cmetaphasementioning
confidence: 92%
“…For cytogenetic analyses oil palm calli were fi xed in Carnoy fi xative (ethanol-acetic acid 3:1 v/v) overnight and processed according to Feulgen's method: 1 hour hydrolysis in HCl 5 N at room temperature followed by 45 minutes staining with Schiff's Reagent (BDH) (GIORGETTI et al 1995). Stained samples were placed on few drops of 45% acetic acid and squashed for cytological analysis.…”
Section: Culturementioning
confidence: 99%
See 1 more Smart Citation